The Use Of "Stile" In Literature: A Study From The Perspective Of Style As A Linguistic Daviation And Its Implications On Language Teaching - I Nengah Astawa; Ida Bagus Nyoman Warta; Luh Sukanadi; I Nyoman Suwandi; I Gusti Ayu Putu Tuti Indrawati (International Journal of Linguistics and Discourse Analytics, 2022)
The writer of literacy works, in conveying massages to his/her audiences as the result of contemplation may manipulate “style” by style here – which comes from English word – is meant the way of the writer to choose languages in conveying massages to the readers or audiences. Style is marked by the formal language forms, such as: the choice of correct dictions, sentence structure, figurative languages, the use of coherence, etc. So style is the appropriate use of language form in certain context, by certain writer, and certain purposes, etc. The final goal of manipulating style is to give exceedingly real satisfaction to the readers or audiences. And this language style should be taught and practiced to the students in the classroom in order that the students may have understanding of the use of diffrent style of languages other than that normally used in formal style